Conversion of Phenols into Selenophenols: Seleno Newman–Kwart Rearrangement1. Issue 47 (17th September 2013) - Sørensen, Anne; Rasmussen, Brian; Agarwal, Shubham; Schau‐Magnussen, Magnus; Sølling, Theis I.; Pittelkow, Michael
<x xml:space="preserve">Abstract</x> A 'Se'lling point: The first thermally induced OAr→SeAr migration reaction is reported, and it can be used to prepare aryl selenols in three steps from the corresponding phenols. O‐aryl selenocarbamates rearrange to Se‐aryl carbamates via a four‐membered transition state (see scheme). The aryl selenols (isolated as the diselenides) can be prepared by hydrolysis of the Se‐aryl selenocarbamates.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>